Intravenous Treatment With Ibandronate Normalizes Bone Matrix Mineralization and Reduces Cortical Porosity After Two Years in Male Osteoporosis: A Paired Biopsy Study. (February 2014) - Misof, Barbara M; Patsch, Janina M; Roschger, Paul; Muschitz, Christian; Gamsjaeger, Sonja; Paschalis, Eleftherios P; Prokop, Eva; Klaushofer, Klaus; Pietschmann, Peter; Resch, Heinrich
ABSTRACT The spectrum of therapeutic options and the amount of clinical trials for male osteoporosis (mOP) is lower than those for postmenopausal osteoporosis. Therefore, we examined the effects of 24 months of ibandronate (IBN) treatment (3 mg/3 mL intravenously every 3 months) on bone material quality in 19 subjects with mOP within an open‐label, single‐center, prospective phase III study (Eudract number 2006‐006692‐20). Patients (median age [25th, 75th percentiles] 53.0 [44.5; 57.0] years) were included if they had low bone mineral density (BMD) and/or at least one low trauma fracture and no secondary cause of osteoporosis. The primary endpoint was to evaluate IBN effects on cancellous (Cn.) and cortical (Ct.) bone mineralization density distribution (BMDD) based on quantitative backscattered electron imaging (qBEI) of paired transiliacal bone biopsies (baseline, 24 months). Secondary endpoints included changes in areal bone mineral density (BMD by dual‐energy X‐ray absorptiometry [DXA]) and serum markers of bone turnover including type I collagen peptides CrossLaps (CTX), procollagen type 1 amino‐terminal propeptide (P1NP), and osteocalcin (OC). At baseline, cancellous bone matrix mineralization from mOP was lower than published reference data (mean degree of mineralization Cn.CaMean −1.8%, p < 0.01). IBN treatment increased calcium concentrations versus baseline (Cn.CaMean +2.4%, Ct.CaMean, +3.0% both p < 0.01), and reduced heterogeneity of mineralization (Cn.CaWidth −14%, p = 0.044; Ct.CaWidth, −16%, p = 0.001), leading to cancellous BMDD within normal range. IBN treatment was associated with a decrease in porosity of mineralized cortical tissue (−25%, p = 0.01); increases in BMD at the lumbar spine, the femoral neck, and the total hip (+3.3%, +1.9%, and +5.6%, respectively, p ≤ 0.01); and reductions in CTX (−37.5%), P1NP (−44.4%), and OC (−36.3%, all p < 0.01). Our BMDD findings are in line with the reduction of bone turnover markers and the increase in BMD by IBN in our patients and suggest that the latter mainly reflects the increase in matrix mineralization and the reduction of cortical porosity in this cohort with mOP. © 2014 American Society for Bone and Mineral Research.